1996
DOI: 10.1021/bc950073l
|View full text |Cite
|
Sign up to set email alerts
|

Indium-111 Labeling of Low Density Lipoproteins with the DTPA−Bis(stearylamide):  Evaluation as a Potential Radiopharmaceutical for Tumor Localization

Abstract: In order to use the LDL receptor pathway to target radionuclides to cancer sites for imaging and diagnostic purposes, a labeling procedure of LDL with 111In using the DTPA-bis(stearylamide) (L) has been developed. This bifunctional ligand is intended to be incorporated into the phospholipid monolayer of LDL and to specifically chelate the In3+ cation at the surface. The ligand was incorporated into LDL in buffered medium with a 65-80% yield. The L-LDL samples are stable over a 24 h period when examined by dial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 38 publications
(44 reference statements)
1
44
0
Order By: Relevance
“…This is consistent with findings for other lipophilic compounds like indium complexed to DTPA-stearylamide, which did not hinder LDL-specific interactions with cells after incorporation into the lipophilic part of the LDL particles (Jasanada et al, 1996). Yen and co-workers (1995) reported that LDL receptors on Daudi cells were already up-regulated which was reflected by elevated mRNA for LDL receptors and insignificant increase of receptor density after incubation in lipoprotein-deficient medium.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with findings for other lipophilic compounds like indium complexed to DTPA-stearylamide, which did not hinder LDL-specific interactions with cells after incorporation into the lipophilic part of the LDL particles (Jasanada et al, 1996). Yen and co-workers (1995) reported that LDL receptors on Daudi cells were already up-regulated which was reflected by elevated mRNA for LDL receptors and insignificant increase of receptor density after incubation in lipoprotein-deficient medium.…”
Section: Discussionsupporting
confidence: 87%
“…It is commercially available (Aldrich), highly water-soluble, and allows for a simple conjugation chemistry through linkage to the amino functions at the CNT surface. Also, DTPA rapidly cages indium with a highly thermodynamic equilibrium constant (44 Fmoc-Phe-OH (5 equiv) in DMF (6 ml) was added in the presence of Bop͞HOBt͞diisopropylethylamine (DIEA) (5͞5͞15 equiv). The coupling was repeated twice for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Chelation of 111 In with DTPA and other chelating agents form very stable complexes that are commonly used for in vivo biodistribution studies of various therapeutic molecules and their delivery systems (45)(46)(47). The stability constant between DTPA and 111 In has been determined by others to be 1.5 ϫ 10 29 (48), and previous studies have shown that the [ 111 In]-DTPA ligand has a strong chelating effect on the radiometal in human serum (44). Moreover, we characterized the In-DTPA complex using nonradioactive indium by HPLC without any loss of indium, concluding that the chelate is stable under physiological conditions.…”
Section: Methodsmentioning
confidence: 99%
“…A lipophilic derivative of diethylenetriaminepentaacetic acid (DTPA), the N,N9-bis(stearylamide) of DTPA (L), was first incorporated into LDL giving L-LDL conjugates before adding 111-indium to obtain the final tracer 111 In-L-LDL. In vitro experiments demonstrated the stability of the lipophilic anchorage of the chelator, the stability of the indium-111 complexation in plasma, while binding studies showed recognition of the 111 In-L-LDL particles by LDL receptors of A549 cells (Jasanada et al, 1996). These preliminary studies demonstrated that In-L-LDL particles possess suitable properties for evaluation as a potential radiopharmaceutical for tumor localization.…”
mentioning
confidence: 84%
“…For the radiometals detectable by gamma scintigraphy, the radioelement was affixed directly or indirectly to protein residues of Apoprotein B-100 (ApoB), the binding ligand to the LDL cell receptor (R-LDL) (Rosen et al, 1990;Virgolini et al, 1991;Ponty et al, 1993). In these procedures, the radiometal/LDL ratio was kept low to avoid disrupting the 3-dimensional structure of the recognition protein.To localize the radionuclide preferentially on the lipid layer and to minimize the structural modification of ApoB, we have developed a new labeling method using a lipid-chelating anchor (Jasanada et al, 1996). A lipophilic derivative of diethylenetriaminepentaacetic acid (DTPA), the N,N9-bis(stearylamide) of DTPA (L), was first incorporated into LDL giving L-LDL conjugates before adding 111-indium to obtain the final tracer 111 In-L-LDL.…”
mentioning
confidence: 99%